ENHANCING ORGANIZATIONAL SUSTAINABILITY THROUGH GREEN HUMAN RESOURCE MANAGEMENT AND TRANSFORMATIONAL LEADERSHIP: THE MEDIATING ROLE OF WORK ENGAGEMENT - Mohamad Iwan Kusnandar; Tibrani Tibrani; Rona Tanjung; Surya Kusumah; Mohd Asmadi (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2026)
This study examines the influence of Green Human Resource Management (GHRM) and Transformational Leadership on Organizational Sustainability, with Work Engagement as a mediating variable in the context of international resort hotels in Lagoi, Bintan, Indonesia. Grounded in Ability-Motivation-Opportunity Theory, Social Exchange Theory, and Resource-Based View, this research employed a quantitative approach using survey data collected from 150 employees and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that GHRM and Transformational Leadership significantly and positively affect Work Engagement and Organizational Sustainability. Work Engagement was also found to have a significant positive effect on Organizational Sustainability. Furthermore, mediation analysis confirmed that Work Engagement partially mediates the relationships between GHRM and Organizational Sustainability as well as between Transformational Leadership and Organizational Sustainability. The findings highlight that sustainability performance in the hospitality sector can be strengthened not only through green HR practices and transformational leadership, but also through fostering employee psychological engagement. This study contributes to the sustainability and hospitality management literature by offering an integrated model linking organizational practices, leadership, and employee engagement to sustainability outcomes, while also providing practical implications for managers seeking to enhance long-term sustainability performance through people-centered strategies. Keywords : Green Human Resource Management, Transformational Leadership, Organizational Sustainability, Work Engagement